Paradigma Etika Publik dalam Kearifan Lokal Pela - John Christian Ruhulessin (Jurnal Filsafat "WISDOM", 2019)
ABSTRACT This paper is based on the basic preposition that local wisdom contains values of virtue that can contribute to the development of public ethics. By examining the Pela cultural institutions in Maluku, this paper intends to answer two main questions: what is Pela’s value of virtues and how to link these values in the framework of developing public ethics relevant to inclusive humanity. The writing aims to offer a thought about public ethics by digging its source from one of the local wisdom of the people of Maluku, namely Pela. The development of the public ethics perspective refers to the concern about the actual context of society, namely pluralism, ethnicity and religion. In this paper, in addition to literature review, the author also uses participatory observation methods and in-depth interviews as data collection techniques, while data analysis is done in the groove of attending, telling, transcribing, analyzing, reading and rewriting. Through this paper, the author arrives at the finding that not only religions are the source of the values of virtue, but also local wisdom (local genius). Pela also has the values of the virtue, such as brotherhood, equality and goodness. The excavation and discovery of these values contribute to theoretical thinking and public ethical praxis, particularly in a pluralistic Indonesian context. Keywords: Pela, public ethics, pluralism, local wisdom.